Detection of Ureaplasma Species in Urogenital Samples by Real-Time PCR in Suspected Sexually Transmitted Infection Patients Attended in Evercare Hospital Dhaka in 2022 - Hasan, Nazmul; Rahim, Rummana; Hasan, Abu; Rahman, Mizanur (Pulse, 2024)
Background: Sexually Transmitted Infections (STIs) are a continual and under-diagnosed disease. Mycoplasma hominis (M. hominis), Ureaplasma urealyticum (U. urealyticum), Ureaplasma parvum (U. parvum) are potential pathogens for urogenital infection of males and females. However, the association of these pathogens with STIs in our country is not yet reported. To determine the existence of M. hominis, U. urealyticum, U. parvum urogenital samples from suspected STIs patients who attended Evercare Hospital Dhaka were investigated. Materials and methods: Extracted DNA from urine, prostatic secretion, urethral swab, and high vaginal swab as per clinician’s recommendation from 50 cases already tested negative for Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium, Trichomonas vaginalis were used in this study from February 2022 to August 2022. Extracted and stored DNA were screened by multiplex real-time PCR for M. hominis, U. urealyticum, U. parvum. Result: Ureaplasma was detected in 12 (24%) samples, U. parvum in 9 (75%), and U. urealyticum in 3 (25%) samples. No pathogens were isolated by routine culture from any of these samples. The positivity rate was more frequent in males (66.6%) than females (33.4%) and in the age group between 19-40 years old. Conclusion: Our data show a significant association of Ureaplasma in STIs patients who attended this hospital. Large scale study is recommended for exploring the prevalence in the community and the role of this pathogen in STIs. Pulse Vol.15, 2023 P: 5-8